O autofinanciamento de campanhas eleitorais sob a égide do princípio da isonomia: uma análise a partir das eleições municipais de 2016 - Raphael Rodrigues Ferreira (2018)
The present work seeks to understand, under the aegis of the principle of electoral isonomy, the self-financing of electoral campaigns that, in the municipal elections of 2016, was limited to the ceiling of expenses related to the position that the candidate intended to compete. To do so, based on an empirical research, the dissertation reveals and analyzes data related to campaign revenues of all candidates for mayor and vice mayor who disputed the first round of the 2016 elections, confronting them with other indicators, some other social, geographic and political nature. In addition, the research was based on historical-legal, legal-understanding and legalpurpose investigations, so that it became possible to understand the evolution of the legislation regarding this type of campaign financing in Brazil as well as the positioning of jurisprudence and doctrine on the subject. In the end, it could be concluded that self-financing, with the limits up to then, contradicts the principle of electoral isonomy, since, as it turned out, the rule was, as a general rule, insufficient to mitigate, in elections, the effects of the difference in economic power between the evaluated candidates.